Main Stages of Applying Innovative Technologies in Sports Activities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the key components of implementing the latest digital innovations in sports activities. The focus is on utilizing these advanced technologies to enhance athletic performance, explore new sports techniques, and address the challenges faced in team sports. The study also examines large-scale digitization in sports, the integration of artificial intelligence, and the application of best practices from leading countries in this field. Additionally, the article highlights the disparities between team sports and individual sports, such as martial arts, and explores strategies to enhance team sports through technological advancements.